“TWO PLANS AND TWO MARSHALS” IN THE LIGHT OF YUGOSLAV-AMERICAN RELATIONS (1947-1951) (Heritage, 2022)
This paper aims to analyze the Yugoslav attitude towards the program of the economic recovery of European economies, which was entitled after US Secretary of State George Marshall, but at the same time a kind of American political agenda in the early phase of the Cold War. The proclamation of the Marshall Plan coincided with the period of the beginning of the First Five-Year Plan for the Economic Development of Yugoslavia, in the time of pronounced needs for economic assistance from abroad. The position of Yugoslavia, located "between the two Plans" and the course of Yugoslav-American relations during the observed period from 1947 to 1951, was significantly reflected in the split between Marshal Tito and Stalin. Moving away from close political, economic, and ideological allies influenced Yugoslav foreign policy of seeking space in the Cold War world. Considering a wide range of published and unpublished, both Yugoslav and American sources, and clarifying the characteristics of the Yugoslav economic system, this paper will follow the unbreakable links between the needs of the economy and the dictates of foreign policy.
Keywords: Marshall Plan, First Five-Year Plan, Yugoslav-American relations, Cold War, Yugoslav Self-Management, Economic Aid